Hakikat Perlindungan Anak Dan Perlindungan Perempuan - Mentari, Vennya Agna; Havid, Trio Lukmanul; Aripin, Iiz Tazul; Mufti, Zaenul; Jamarudin, Ade; Saepullah, Usep (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: This paper discusses the importance of protecting women and children from violence and harassment. This article emphasizes the role of education in shaping the character of future generations and highlights the need for preventive action to ensure the safety and well-being of women and children. This article also examines the legal framework for protecting women and children and the various forms of violence they may face. The methodology used in this article is normative legal research, and the discussion is focused on human rights perspectives and expert opinions. The legal basis for the protection of women and children is regulated in Law Number 12 of 2022 concerning Sexual Violence and Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The definition of a child is based on age, but there is no agreement on an age limit. Child protection is mandated by various laws, including the Convention on the Rights of the Child. The function of law is to create a harmonious, balanced, peaceful and just relationship between legal subjects. Preventive legal protection aims to prevent violence and crimes against women and children. Law enforcement is not only about implementing regulations but also about implementing court decisions. Child protection is very important for the future of a nation, and it involves the whole society. Child protection includes their physical, mental and social development. Protection of human rights, especially for women and children, must be done fairly and politely. The basis for legal protection is outlined in various laws, including those related to sexual violence and domestic violence.Keywords: Legal protection, women, children Abstrak: Tulisan ini membahas pentingnya perlindungan terhadap perempuan dan anak-anak dari kekerasan dan pelecehan. Artikel ini menekankan peran pendidikan dalam membentuk karakter generasi masa depan dan menyoroti perlunya tindakan preventif untuk memastikan keselamatan dan kesejahteraan perempuan dan anak-anak. Artikel ini juga membahas kerangka hukum untuk melindungi perempuan dan anak-anak serta berbagai bentuk kekerasan yang mungkin mereka hadapi. Metodologi yang digunakan dalam artikel ini adalah penelitian hukum normatif, dan diskusi difokuskan pada perspektif hak asasi manusia dan pendapat para ahli. Basis hukum untuk perlindungan perempuan dan anak-anak diatur dalam Undang-Undang Nomor 12 Tahun 2022 tentang Kekerasan Seksual dan Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga. Definisi anak didasarkan pada usia, tetapi tidak ada kesepakatan tentang batas usia. Perlindungan anak diamanatkan oleh berbagai undang-undang, termasuk Konvensi Hak Anak. Fungsi hukum adalah menciptakan hubungan yang harmonis, seimbang, damai, dan adil antara subjek hukum. Perlindungan hukum preventif bertujuan untuk mencegah kekerasan dan kejahatan terhadap perempuan dan anak-anak. Penegakan hukum tidak hanya tentang menerapkan peraturan tetapi juga tentang menerapkan keputusan pengadilan. Perlindungan anak sangat penting untuk masa depan sebuah bangsa, dan melibatkan seluruh masyarakat. Perlindungan anak meliputi perkembangan fisik, mental, dan sosial mereka. Perlindungan hak asasi manusia, terutama bagi perempuan dan anak-anak, harus dilakukan dengan adil dan santun. Dasar perlindungan hukum diuraikan dalam berbagai undang-undang, termasuk yang terkait dengan kekerasan seksual dan kekerasan dalam rumahKata kunci: Perlindungan hukum, Perempuan, anak